A Preliminary Survey of TQM Knowledge and Case Study Findings Analysis among OSH Profession Community in Malaysia - Kang, Eng Thye; Ramanchandram, Rajoo; Idrus, Mohd Rushdi (2017)
The Total Quality Management (TQM) principles can widely be seen in most audit assessment frameworks such as the ISO Quality, Environmental and OSHAS 18001 as well as the ILO’s OSHMS. Nevertheless, there is a negative report by The International Labour Organization’s Caribbean Office and Multidisciplinary Advisory Team about the misuse of TQM concept by individual and organization that contradicts the original TQM teaching in the Occupational Safety and Health (OSH) context. The purpose of this study is to identify the level of understanding of TQM knowledge among OSH professionals in Malaysia. Apart from that, this study is also conducted to identify whether auditors are able to come to a same conclusion based on a case study given. The results show that 101 (91.8%) respondent agreed that TQM principles is important to strengthen the OSH management performance. However, all of the respondents failed to identify correctly the name of Deming’s book and his core teachings.The case study results implied that there are differences of opinions among OSH professionals. Such results put a suspicious light on the effectiveness of audit findings and their validity in helping to improve the OSH performance.